(untitled) (Experimental biology, 2016)
In this article environmental pollution by heavy metals and negative influence on a human body is considered. According to domestic and foreign scientific sources it was carried out the review of literatures on cytomorphological changes in system of blood at influence of heavy metals. In environment a human body and animals often are exposed on separate negative influence of heavy metals. It is established that the mankind can be affected by several metals and toxic effects of each other can strengthen or lower set of metals. Research of cytomorphological and cytochemical changes of blood cells at influences of heavy metals can prevent an organism from pathological processes at influences of heavy metals. Thus, the question studying of the combined impact of heavy metals on an organism was formulated.